Types and Morphometric Study of Calcaneal Articular Facets on Human Tali of Thai Population - Phunchago,Nichapa (Sociedad Chilena de Anatomía, 2018)
SUMMARY: Patterns and variant morphometries of calcaneal articular facets on talus are concerned before performing of joint ankle surgery, including used as a sex determination. Types of talar facets have been documented in many populations except in Thai race. Therefore, this study attempted to classify the types of talus facets and to measure the facet lengths on dried tali of Thais. The 372 dried tali (204 males, 168 females) from Khon Kaen University Bone Collection were observed for variant types and measured for their facet lengths. The facets were classified into 6 types: type I, tree facet are separated (1.88 %); type II (A), the anterior and middle facets are partially connected with predominant ridge (34.68 %); type II (B), the anterior and middle facets are partially connected with slight ridge (32.53 %); type III, the anterior and middle facets are fully fused to form a single facet (2.96 %); type IV, the anterior and middle facets are partially separated by a ridge and partly by a groove (27.42 %); type V, all facets are continuous fused to form a single facet (0.54 %). In addition, the morphometric lengths of AP (anterior to posterior process) and ML1&2 (medial to lateral process) in male are significantly greater than those of female. The AP, ML, and ML2 of male are 56.71±0.16, 41.63±0.18, and 37.85±0.36 mm, while of female are 51.21±0.12, 37.74±0.16, and 33.85±0.28 mm, respectively. This incidence can be used as ankle surgery consideration and an anthropological marker for sex determination of unidentified talus.